43rd Winter School on Vibroacoustical Hazards Suppressions - BUKOWSKI, Roman (Archives of Acoustics, 2015)
Traditionally, the 43rd Winter School on Vibroacoustical Hazards Suppressions national conference was organized by Upper Silesian Division of the Polish Acoustical Society (main organizers) and by The Committee on Acoustics of The Polish Academy of Sciences (co-organizer). The Conference, as in previous years, was held in Szczyrk. The conference is a forum for all environmental vibroacoustic fields. Particularly it concerns traffic noise, industry noise, vibroacoustics of machines, room acoustics, building acoustics, noise protection and similar problems. Works which are presented during the School are theoretical, experimental, measuring, technical, applied and normative. The School lectures and other conference materials will be published in the “Materials of the XLIII Winter School on Vibroacoustical Hazards Suppressions” (in Polish) edited by dr. Roman Bukowski. This publication will be intended for participants of the School and for many libraries in Poland. Moreover you can find in this issue abstracts of some lectures presented at conference.